A PESQUISA GREAT PLACE TO WORK E SUA IMPORTÂNCIA PARA O DESENVOLVIMENTO ORGANIZACIONAL DE GRANDES EMPRESAS BRASILEIRAS - Galdino da Silva Souza, Levi (2023)
In the current scenario of globalization and business internationalization, companies are increasingly involved in team formation, attracting and retaining the most qualified professionals in their sector. Therefore, it is relevant to explore the relationship between the evaluation of Great Place to Work (GPTW) and the organizational development of large companies, as GPTW is a global consultancy that aims to assist organizations in achieving better results. Thus, the general objective is to analyze the impact of GPTW research on the organizational development of large Brazilian companies. This bibliographic work relies on research conducted by social psychologist Edgar H. Schein (2010), author of the book Organizational Culture and Leadership, and other authors such as Lencioni (2012), Pereira (2019) and Kielwagen and Souza (2013). We aim to reflect on the impact of this consultancy on the companies that use it, and based on Kurt Lewin's (1995) organizational development methodology, we identify areas for improvement in team management, leadership development, and the overall work environment. As a result, some elements that can make companies better places to work were identified, and it was highlighted that companies recognized by GPTW tend to attract the best talents, resulting in significant competitive advantages in their market. Furthermore, through this research, we are contributing to the production of academic knowledge in the field of Applied Foreign Languages for International Negotiations studies, especially regarding corporate development, aiding in the understanding of how GPTW research can contribute to a better work environment among companies.